Review of An Insider’s Guide to the Japanese Martial Arts: A New Look at Japan’s Fighting Traditions, by Alexander Bennett - Eckford, David (Revista de Artes Marciales Asiáticas, 2023)
This review addresses An Insider’s Guide to the Japanese Martial Arts: A New Look at Japan’s Fighting Traditions by Alexander Bennett, published in 2023 by Tuttle Publishing. The Japanese martial arts and Japan have long attracted practitioners from around the globe travelling to Japan, hoping to further the knowledge of their chosen martial art. Far from being a recent trend, records of such travels have graced the martial arts literature for decades. This volume offers a neatly packaged representation of the Japanese martial arts written in an approachable manner by a bilingual, bicultural, academic, martial arts researcher and high-ranking exponent. Stocked with educational and credible material and delivered in an affable tone, this book provides a thorough coverage of the Japanese martial arts from their early past to the present day. In addition, practical and indispensable information for surviving and making the most out of one’s stay in Japan is presented. Invaluable to the practitioner with their sights set on studying martial arts in Japan, this publication goes way beyond and presents a plethora of information, both historical and contemporary, which will captivate all those studying the arts, regardless of their domicile. This valuable contribution to the martial arts literature is an enjoyable and educational walk through the Japanese martial arts that will benefit the uninitiated, novices, and seasoned veterans alike. Keywords: Japanese martial arts; Japanese martial history; studying martial arts in Japan; Japanese culture